Analysis of Service Quality JKN Mobile Application Toward Participants Satisfaction of the Health Social Security Implementing Agency (BPJS) Tegal Regency - Putri, Deva Amanda; Maharani, Chatila (MEDIA ILMU KESEHATAN, 2023)
Background: JKN Mobile is an innovation by BPJS Kesehatan to provide service access easier for their participants. JKN Mobile application can be accessed everytime and everywhere while continuing to provide optimal service quality for user satisfaction.Objective: This study aims to analyze the correlation between service quality (tangile, reliability, responsiveness, assurance, and empathy) with satisfaction of JKN Mobile’s users at Tegal Regency.Methods: Type of quantitative research using cross sectional research design. Sampling method using accidental sampling technique. Total sample 100 respondents using Lameshow sample size formula. The research instrument used questionnaire.Results: Based on the fisher exact statistical test on the service quality with satisfaction the result is tangible (p=0,001), reliability (p=0,000), responsiveness (p=0,000), assurance (p=0,000), dan empathy (p=0,000). Conclusion: There was a significant relationship between service quality with satisfaction.